An Australian newspaper campaign and government vaccination policy. (1st June 2021) - LeMonde, Julia
Abstract : News Corp Australia recently initiated a campaign to pressure the Australian government to amend its childhood vaccination policies. In 2015, the government legislated amendments in accord with the campaign's demands despite criticism from experts in children's health and vaccine advocacy, research and surveillance. A narrative review was conducted of newsprint articles which featured during the media campaign between 2013 and 2015. Findings indicate that the campaign focused on moral attributes that stigmatised conscientious objector parents as 'anti-vaxers', baby-killers, and hippies and loons. The decision to change vaccination legislation is compatible with the creation of a media-manufactured moral panic concerning conscientious objector parents. When deconstructing moral panics, a careful analysis of the roles of different media sectors is important. The alliance between News Corp Australia and Australian politicians to introduce new vaccination legislation represents an innovation in health policy formation which illustrates how expert opinion on public health policies can be sidelined.